1533 The Effect of Hip Fracture Anatomy and The Modality of Surgery on Red Blood Cell Transfusion and Mortality: A Retrospective Analysis. (12th October 2021) - Greenhalgh, M; Gowers, B; Iyengar, K; Adam, R
Abstract: Introduction: Hip fractures are common, with most requiring surgical management. Blood loss occurs from the fracture and intraoperatively. Often, blood transfusions are required. Hip fractures can be classified by their anatomy: intracapsular, intertrochanteric or subtrochanteric fractures. This study assesses the effect of fracture pattern and operation performed on transfusion rates within our centre. We aim to identify the patients most likely to require transfusion early, to improve outcomes. Method: A retrospective cohort study of 324 consecutive hip fracture patients presenting to a district general hospital over one year. Data was collected from electronic patient records, the local transfusion laboratory, and the national hip fracture database. Results: 324 hip fractures were divided into 188 (58%) intracapsular, 121 (37%) intertrochanteric and 15 (5%) subtrochanteric fractures. The most common operation performed was hemiarthroplasty (128), followed by dynamic hip screw fixation (75). 75 (23%) of all patients received a blood transfusion. 28 (15%) of intracapsular, 42 (35%) of intertrochanteric and 5 (33%) of subtrochanteric fractures received transfusions. 47% of long intramedullary nails, 45% of short intramedullary nails, 29% of dynamic hip screws, 18% of hemiarthroplasties and 9% of total hip arthroplasties resulted in blood transfusions. One-year mortality in the transfused cohort was 52% and 30.5% in non-transfused. Conclusions: Almost a quarter of hip fracture patients received a blood transfusion, which was associated with an increased risk of mortality. Intertrochanteric fractures most commonly led to a transfusion. The operation most associated with transfusions were long intramedullary nailings, and total hip arthroplasties were the least.